DETERMINAN FUNDAMENTAL HARGA SAHAM PADA PT BUKALAPAK.COM TBK - Putri Permata Sari; Salman, Muhammad; Nurliza Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of Net Profit Margin, Earnings Per Share, and Debt to Equity Ratio on the stock price of PT Bukalapak.com Tbk. The data used in this study is secondary data collected from the IDX Syariah, the company's annual report, and monthly financial ratio data in the financial statements of PT Bukalapak.com Tbk for the period September 2021 to December 2024. The data obtained were analyzed using the Statistical Package for Social Science (SPSS) 23. The data analysis method used in this study was multiple linear regression with three approaches: Net Profit Margin (NPM), Earnings Per Share (EPS), and Debt to Equity Ratio (DER). The results of this study indicate that Net Profit Margin and Earnings Per Share affect the stock price. Meanwhile, the Debt to Equity Ratio does not affect the stock price of PT Bukalapak.com Tbk. Simultaneously, Net Profit Margin, Earnings Per Share, and Debt to Equity Ratio influence the stock price of PT Bukalapak.com Tbk.